High-pressure treatment enhanced aromatic compound concentrations of melon juice and its mechanism - Liu, Xiao; Wang, Ruiqi; Liu, He; Wang, Yubin; Shi, Yue; Zhang, Chao (Frontiers in Nutrition, 2022)
The flavor deterioration blocks the development of the melon juice. The effects of ultra-high temperature (UHT) and high pressure (HP) treatments on the aromatic compound concentrations of melon juice and its mechanism were explored with the fresh juice as the control. A total of 57 volatile compounds was identified by gas chromatography tandem mass spectrometer analysis. β-ionone was detected as the major aromatic component of melon juice for the first time. The HP at 200 MPa for 20 min increased the total volatile concentration of melon juice by 1.54 and 3.77 times of the control and UHT, respectively. Moreover, the sum concentration of major aromatic component in the HP treatment was 1.49 and 5.94 times higher than that of the control and UHT, respectively. The HP treatment raised the concentration of volatile component and aromatic components of melon juice by reducing their surface tension.